Литниковые системы для получения чугунных отливок с дифференцированной структурой и свойствами модифицированием исходного расплава в литейной форме - Фесенко, М.А.; Фесенко, А.Н.; Могилатенко, В.Г. (Металл и литье Украины, 2018)
В работе предлагаются и исследуются новые технологические варианты производства чугунных отливок с дифференцированной структурой и свойствами из одного расплава, которые базируются на способе модифицирования базового жидкого чугуна непосредственно в литейной форме. В роботі запропоновано та досліджено нові технологічні варіанти виробництва чавунних виливків з диференційованою структурою та властивостями з одного розплаву, які базуються на способі модифікування базового рідкого чавуну безпосередньо в ливарній формі. The paper proposes and investigates new technological options for the production of iron castings with a differentiated structure and properties from one single melt, which are based on the modification of the base liquid iron directly in the mold. Castings are selected as research objects - horizontal and vertical slabs, as well as bars, which simulate typical industrial castings, such as an excavator bucket tooth, plowshare plow blades, knives for cutting paper, rubber and other materials, hammer crushers, armor plates, and cheeks etc.